-7-4(-z-6)=6(-4z-4)-6

Simple and best practice solution for -7-4(-z-6)=6(-4z-4)-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7-4(-z-6)=6(-4z-4)-6 equation:


Simplifying
-7 + -4(-1z + -6) = 6(-4z + -4) + -6

Reorder the terms:
-7 + -4(-6 + -1z) = 6(-4z + -4) + -6
-7 + (-6 * -4 + -1z * -4) = 6(-4z + -4) + -6
-7 + (24 + 4z) = 6(-4z + -4) + -6

Combine like terms: -7 + 24 = 17
17 + 4z = 6(-4z + -4) + -6

Reorder the terms:
17 + 4z = 6(-4 + -4z) + -6
17 + 4z = (-4 * 6 + -4z * 6) + -6
17 + 4z = (-24 + -24z) + -6

Reorder the terms:
17 + 4z = -24 + -6 + -24z

Combine like terms: -24 + -6 = -30
17 + 4z = -30 + -24z

Solving
17 + 4z = -30 + -24z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '24z' to each side of the equation.
17 + 4z + 24z = -30 + -24z + 24z

Combine like terms: 4z + 24z = 28z
17 + 28z = -30 + -24z + 24z

Combine like terms: -24z + 24z = 0
17 + 28z = -30 + 0
17 + 28z = -30

Add '-17' to each side of the equation.
17 + -17 + 28z = -30 + -17

Combine like terms: 17 + -17 = 0
0 + 28z = -30 + -17
28z = -30 + -17

Combine like terms: -30 + -17 = -47
28z = -47

Divide each side by '28'.
z = -1.678571429

Simplifying
z = -1.678571429

See similar equations:

| -9m+11=-8+4 | | Q=r-s/s | | 4c(c+3)=84 | | 121=(x+6)(20-4x) | | 4m-8=44 | | 2k+1=k+5 | | 1/5(10x-5)=1/4(10x-8) | | y^2-23y-28=0 | | -v^2+11v-28=0 | | 4+9x^2=40 | | -u^2+8u-12=0 | | 6n^2=8n+11 | | 3x^2+14x+144=0 | | A+3b+70=100 | | x^2+14x+144=0 | | 66000=3x^2+4x+2 | | 25s^4t^7/5s^3t^9 | | 8xy-6xy+2xy= | | 62=3y+17 | | 0=-2/((m-2)(m-4)) | | x+3x-24= | | 0=-2/(m-2)(m-4) | | 3y^2+2x-3=0 | | 36k^2=49 | | x-8x+15= | | 3x-10x=0 | | 27x^4-72x^2+8x+36=0 | | x+20x+36= | | -8-(x/2)=-10 | | y+112=805 | | 29n=986 | | x/5-8=1 |

Equations solver categories